(untitled) (Contemporary Journal of Social Science Review, 2025)
Decades ago, shopping was considered a leisure activity by many Pakistani families on weekends. People used to buy groceries, other fast-moving consumer goods, and utilities from the general locality store. But with the modernization and introduction of smart devices, people now have access to information from all around the world. People now delve into the ocean of the internet, browse and select the product, and can pay in the most convenient way they like. Where technology has facilitated humans, it has also influenced human health and made them technology-dependent, drifting away from nature. Retail stores were considered to be the point where salesmen had direct contact with customers, but now people don’t look for just products or services, they are more looking for an experience. So, in this regard, this study was conducted to examine the impact of major internal and external factors that affect customer experience in retail shops in Multan, Punjab, Pakistan. The data were collected with the help of carefully designed questionnaire from a sample of 200 respondents using convenience and random sampling techniques. Data then were transformed into computer, arranged, analyzed, and interpreted using software SPSS version 25. The results revealed that inside store temperature and accessibility to the store were the main and most prioritized factors that enhanced the customer shopping experience in an experiential retail setting. Also, it was discovered that out of all variables that were studied in this research 7 variables were found to have a moderate correlation with customer loyalty. In contrast, 3 were found to have a positive weak correlation, and only customer satisfaction was found to have a highly positive correlation with customer loyalty. Results also exhibited the positive impact of experiential retail practices on customer satisfaction and customer loyalty.